Free Trade Agreements, Customs Unions In Disguise? - Feodora Teti; Gabriel Felbermayr; Erdal Yalcin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We document a hitherto overlooked stylized fact: countries' external tariff schedules are surprisingly similar. The correlation is particularly striking for countries belonging to the same deep preferential trade agreement (PTA). We show that most of this is due to selection effects rather than to ex post convergence. This has an important implication: In most PTAs, for a vast majority of products, trade deflection is not profitable even in the absence of costly rules of origin.
Keywords: F10; F13; F15; 330